Main sociocultural factor interfering the development of the speaking skill - Bermudez Avendaño, Karla Vannesa | Espinoza Meléndez, Kevin Smith | Calderón, Miltón Ariel (NI UNAN, Managua, Nicaragua, 2019)
The ability to speak a foreign language is often considered one of the most difficult aspects of language learning. In reality, many English language learners find it difficult to express themselves in spoken language in the target language. Each student has their own problems. The purpose of this study was to investigate the speaking problems of the students at Guardabarranco Public School and the socio-cultural factors interfering their speaking skill. The subjects of the study were 30 students from 11th grade, and 1 teacher of English. Class observation guides, student questionnaires, and an interview to the teacher were used as data collection techniques. The findings suggest students are not really conscious of the influence that the socio-cultural factors studied in this research have on the effectiveness of the speaking skill. Learning a new language means learning a new culture, too. The primary expression of a culture is the Language, belonging to that culture. EFL is a challenge for Guardabarranco 11th grade students given that the sociocultural and linguistic learning context they are learning does not provide the ideal environment for learning- especially the speaking skill. The Nicaraguan native language and socio-economical background of EFL learners also impact the development of the speaking skill
Seminario-(Licenciadas en Ciencias de la Educación con mención en Inglés)-Universidad Nacional Autónoma de Nicaragua.
Keywords: Enseñanza-Aprendizaje | Inglés-Enseñanza | Inglés-Seminarios-2019 | Habilidades del lenguaje | Comunicación oral-Estudio y enseñanza